2015
DOI: 10.1007/s11606-015-3323-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Attending Practice Style on Generic Medication Prescribing by Residents in the Clinic Setting: An Observational Study

Abstract: BACKGROUND: Despite increased emphasis on costconsciousness in graduate medical training, there is little empirical evidence of the role of attending physician supervision on resident practice in this area. OBJECTIVE: To study whether the prescribing practices of attendings influence residents' prescribing of brand-name statin medications in the ambulatory clinic setting. DESIGN AND PARTICIPANTS: A retrospective study of statin prescriptions by residents at two internal medicine residency programs, using elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
(23 reference statements)
1
27
0
Order By: Relevance
“…Evidence suggests that factors that influence physician test-ordering behaviors range broadly beyond physician knowledge and local Estimates reported from six models: (1) intent-to-treat (two arms) comparing control vs. intervention, (2) post-hoc model (two arms) comparing intervention vs. control by day post intervention, (3) post-hoc model (three arms) comparing controls vs. physicians randomized to the intervention who opened the intervention e-mail vs. those who did not open the intervention e-mail, (4) post-hoc model (three arms) comparing controls vs. physicians randomized to the intervention who accessed the dashboard vs. those who did not access the dashboard, and (5) secondary outcome: controls vs. intervention for laboratory orders not targeted by the intervention p-value <0.05 practice patterns. 10,[27][28][29] Residents may be reluctant to reduce ordering because of perceived institutional or attending expectations, risk-aversion, and uncertainty about potential harms (e.g., lack of cost transparency). 14,30 Interventions that aim to influence physician behavior should be thoroughly tested prior to broad implementation to avoid unanticipated effects, particularly in areas of practice with high clinical uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that factors that influence physician test-ordering behaviors range broadly beyond physician knowledge and local Estimates reported from six models: (1) intent-to-treat (two arms) comparing control vs. intervention, (2) post-hoc model (two arms) comparing intervention vs. control by day post intervention, (3) post-hoc model (three arms) comparing controls vs. physicians randomized to the intervention who opened the intervention e-mail vs. those who did not open the intervention e-mail, (4) post-hoc model (three arms) comparing controls vs. physicians randomized to the intervention who accessed the dashboard vs. those who did not access the dashboard, and (5) secondary outcome: controls vs. intervention for laboratory orders not targeted by the intervention p-value <0.05 practice patterns. 10,[27][28][29] Residents may be reluctant to reduce ordering because of perceived institutional or attending expectations, risk-aversion, and uncertainty about potential harms (e.g., lack of cost transparency). 14,30 Interventions that aim to influence physician behavior should be thoroughly tested prior to broad implementation to avoid unanticipated effects, particularly in areas of practice with high clinical uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalists at academic medical centers face growing pressures to develop processes to reduce low‐value care and train residents to be stewards of healthcare resources . Studies have described that institutional and training factors drive residents' resource utilization patterns, but, to our knowledge, none have described what factors contribute to residents' unnecessary laboratory testing. To better understand the factors associated with residents' ordering patterns, we conducted a qualitative analysis of internal medicine (IM) and general surgery (GS) residents at a large academic medical center in order to describe residents' perception of the: (1) frequency of ordering unnecessary inpatient laboratory tests, (2) factors contributing to that behavior, and (3) potential interventions to change it.…”
mentioning
confidence: 99%
“…A study suggested that the post graduate year 1 (PGY1) residents prescribe brand name statins in a manner that reflects their attending physicians, whereas the senior residents prescribe higher cost drugs regardless of the attending practices. 11 This suggests that there is a need to educate across the board. Restricting ourselves to the medical names can also help limit the conflicts of interests the physicians have with the industry.…”
mentioning
confidence: 99%